Impact of beta-blockers on mortality and cardiovascular disease outcomes in patients with obstructive sleep apnoea: a population-based cohort study in target trial emulation frameworkResearch in context - Anthony Chen; Chengsheng Ju; Isla S. Mackenzie; Thomas M. MacDonald; Allan D. Struthers; Li Wei; Kenneth K.C. Man (Elsevier, 2023)
Summary: Background: There is no real-world evidence regarding the association between beta-blocker use and mortality or cardiovascular outcomes in patients with obstructive sleep apnoea (OSA). We aimed to investigate the impact of beta-blocker use on all-cause mortality and cardiovascular diseases (CVDs) in patients with OSA. Methods: We conducted a target trial emulation study of 37,581 patients with newly diagnosed OSA from 1st January 2000 to 30th November 2021 using the IMRD-UK database (formerly known as the THIN database). We compared the treatment strategies of initiating beta-blocker treatment within one year versus non-beta-blocker treatment through the method of clone-censor-weight. Covariates, including patients' demographics, lifestyle, comorbidities, and recent medications, were measured and controlled. Patients were followed up for all-cause mortality or composite CVD outcomes (angina, myocardial infarction, stroke/transient ischaemic attack, heart failure, or atrial fibrillation). We estimated the five-year absolute risks, risk differences and risk ratio with 95% confidence intervals (CIs) with standardised, weighted pooled logistic regression, which is a discrete-time hazard model for survival analysis. Several sensitivity analyses were performed, including multiple imputation addressing the missing data. Findings: The median follow-up time was 4.1 (interquartile range, 1.9-7.8) years. The five-year absolute risk of all-cause mortality and CVD outcomes were 4.9% (95% CI, 3.8-6.0) and 13.0% (95% CI, 11.4-15.0) among beta-blocker users, and 4.0% (95% CI, 3.8-4.2) and 9.4% (95% CI, 9.1-9.7) among non-beta-blocker users, respectively. The five-year absolute risk difference and risk ratio between the two groups for all-cause mortality and CVD outcomes were 0.9% (95% CI, −0.2 to 2.1) and 1.22 (95% CI, 0.96-1.54), and 3.5% (95% CI, 2.1-5.5) and 1.37 (95% CI, 1.22-1.62), respectively. Findings were consistent across the sensitivity analyses. Interpretation: Beta-blocker treatment was associated with an increased risk of CVD and a trend for an increased risk of mortality among patients with OSA. Further studies are needed to confirm our findings. Funding: Innovation and Technology Commission of the Hong Kong Special Administration Region Government.